STRATEGIC MARKETING MANAGEMENT OF ISLAMIC EDUCATIONAL INSTITUTIONS IN THE DIGITAL ERA - Rosadi, Nur Amelliany; Sa’diyah, Maemunah; Sastra, Ahmad (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2025)
The decline in student enrollment at Islamic educational institutions has become a serious challenge in maintaining both their existence and educational quality, including at SMP Qur’an As-Salam Pekanbaru. This condition requires structured, systematic, and adaptive marketing management that responds to social, cultural, and technological developments. Therefore, this study aims to analyze the implementation of marketing management based on the Planning, Organizing, Actuating, and Controlling (POAC) framework in enhancing the attractiveness and image of the institution. This research employed a descriptive qualitative approach, with data collected through in-depth interviews, direct observation, and documentation. The research subjects consisted of school leaders, administrators, teachers, and parents who were actively involved in marketing strategies. Data analysis was carried out through data reduction, data display, and conclusion drawing, while maintaining validity through source and method triangulation. The results of the study indicate that marketing planning at SMP Qur’an As-Salam is designed based on its Qur’anic vision and mission, emphasizing Islamic character education, Qur’an memorization, and academic quality. In terms of organizing, the institution established a special team responsible for promotional activities, both conventional and digital. The implementation of strategies combined direct promotion (social gatherings, brochures, banners, community activities) with digital promotion (social media, websites, and educational content). Evaluation or controlling was conducted periodically through monthly and annual meetings, which assessed the effectiveness of promotional media, enrollment levels, and community satisfaction. Although the POAC-based strategy has proven effective in improving the school’s image and community interest, its effectiveness is reflected in the increasing number of inquiries and student registrations, higher community participation in school activities, and more positive feedback from parents and stakeholders. the study also found limitations, including weak digital media management, lack of innovation in promotional content, and limited promotional facilities. These factors reduce the institution’s competitiveness amid the increasingly intense landscape of Islamic education. In conclusion, the application of POAC-based marketing management at SMP Qur’an As-Salam has been effective in strengthening institutional identity despite the decline in enrollment. However, improvements are still needed in digital marketing, market research, and external collaboration. This study recommends continuous innovation, training in digital media management, and collaborative strategies with stakeholders to expand outreach and ensure the sustainability of Islamic educational institutions in the modern era.